High-Risk Non-syndromic Hearing Loss Associated with Gene Mutations by Using DNA Marker Screening - Yasin Kareem Amin (Novel Research Aspects in Medicine and Medical Science Vol. 1, 2023)
This study was aimed to screen DNA in high-risk Non-syndromic hearing loss patients in Arbil city. Congenital hearing loss (hearing loss present at birth) is one of the most prevalent chronic conditions in children. Hearing loss has been described as the most common disabling condition worldwide. Congenital hearing loss (hearing loss present at birth) is one of the most prevalent chronic conditions in children. Many deafness and hearing problems cases were documented in our region. This research screened 132 blood samples from 132 participants (80 newborns and 52 individuals) aged between 14-22 years at Hiwa Institute for deaf and mutes. MTRNR1 genes were performed for molecular detection of mutant genes. The mutation gene was amplified by multiplex tetra primer PCR. G- mito-1555-F1, mito-1555-R1 (O), mito-1555-F2 (I), and mito-1555-R2. (I) hearing loss mutations were not observed in 132 blood samples from both classes and genotyped in MTRNR1. For mtDNA 12S rRNA mt.1555A>G, no mutant alleles were detected in all of the tests, and no false-positives were identified. On a 2% agarose gel, fifty-two samples were easily separated using all of the primers; two of the primers were outer primers and the rest were inner primers. With 52 molecular samples, two distinct bands (wild type at 254 bp and control at 341 bp) were seen. 28 of the 80 samples had 341 bp control bands. In 80 samples, we looked for mutations but found none. MTRNR1 mutation genes were not present in collected samples in deafness-related mutation. Genetic tests for the deafness gene can better diagnose infant congenital NSHL cases than conventional screening procedures.